Epidemiology, pathogenesis, and treatment of the common cold - Hendley, J. Owen (Semin Pediatr Infect Dis, 1998)
The common cold is an acute illness of the upper respiratory tract caused by a virus acquired from another person. Some viruses that produce colds are capable of infecting an individual repeatedly (eg, respiratory syncytial virus); others, with many serotypes (eg, rhinovirus), infect only once. The sustained epidemic of colds that occurs annually during September through April is explained by successive waves of different viruses moving through a community. The peak incidence of colds occurs in preschool children, who typically sustain at least one illness per month during the epidemic period. Clinical manifestations of colds are largely subjective in adults. Colds in preschoolers differ from those in adults as follows: (1) fever is common in children during the first 3 days; (2) colored nasal secretions may be the only indication of nasal involvement in children; and (3) colds in children last 10 to 14 days, as compared with a duration of less than a week in adults. The paranasal sinuses and the middle ear cavities are commonly involved during viral colds in adults (and presumably in children) in the absence of bacterial superinfection. Cold symptoms are due to the host's response to the virus rather than to destruction of the nasal mucosa. Viral infection of a very limited portion of the nasal epithelium results in an influx of polymorphonuclear leukocytes, cytokine release, and a vascular leak. Colds are self-limited illnesses. Therefore, in the absence of adequate blinding of controls, ineffective treatments erroneously may be considered efficacious. None of the medicines used for symptom relief in colds is curative.